Biomarkers of RV Dysfunction in HFrEF Identified by Direct Tissue Proteomics: Extracellular Proteins Fibromodulin and Fibulin-5 - Běhounek, Matěj; Lipcseyová, Denisa; Vít, Ondřej; Žáček, Petr; Talacko, Pavel; Husková, Zuzana; Kikerlová, Soňa; Tykvartová, Tereza; Wohlfahrt, Peter; Melenovský, Vojtěch; Beneš, Jan; Petrák, Jiří (Circulation. Heart failure, 2025)
BACKGROUND: Right ventricular dysfunction (RVD) is common in patients with heart failure with reduced ejection fraction, and it is associated with poor prognosis. However, no biomarker reflecting RVD is available for routine clinical use. METHODS: Proteomic analysis of myocardium from the left ventricle and right ventricle (RV) of patients with heart failure with reduced ejection fraction with (n=10) and without RVD (n=10) who underwent heart transplantation was performed. Concentrations of 2 ECM (extracellular matrix) proteins with the highest myocardial upregulation in RVD, FMOD (fibromodulin) and FBLN5 (fibulin-5), were assayed in the blood and tested in a separate cohort of patients with heart failure with reduced ejection fraction (n=232) to test for the association of the 2 proteins with RV function and long-term outcomes. RESULTS: Multivariable linear regression revealed that plasma concentrations of both FMOD and FBLN5 were significantly associated with RV function regardless of the RV function assessment method. No association of FMOD or FBLN5 with left ventricular dysfunction, cardiac index, body mass index, diabetes status, or kidney function was found. Plasma levels of FMOD and FBLN5 were significantly associated with patient outcomes (P=0.005; P=0.004). Area under the curve analysis showed that the addition of FBLN5 or FMOD to RV function assessment had a significantly higher area under the curve after 4 years of follow-up (0.653 and 0.631, respectively) compared with RV function alone (0.570; P<0.05 for both). Similarly, the combination of MAGGIC (Meta-Analysis Global Group in Chronic Heart Failure) score, FBLN5, and FMOD had a significantly larger area under the curve (0.669) than the combination of MAGGIC score+RVD grade (0.572; P=0.02). The Kaplan-Meier analysis demonstrated that patients with the elevation of both FMOD and FBLN5 (ie, FMOD >64 ng/mL and FMOD >27 ng/mL) had a worse prognosis than those with the elevation of either FBLN5 or FMOD (P=0.03) demonstrating the additive prognostic value of both proteins. CONCLUSIONS: Our study proposes that circulating levels of FMOD and FBLN5 may serve as new biomarkers of RVD in patients with heart failure with reduced ejection fraction.
Keywords: senioři; Stroke Volume; proteomika; Fibromodulin; Prognosis; Middle Aged; mužské pohlaví; proteiny vázající vápník; Heart Transplantation; Ventricular Function, Right; funkce levé komory srdeční; funkce pravé komory srdeční; srdeční komory; tepový objem; Proteomics; extracelulární matrix - proteiny; ženské pohlaví; prognóza; Humans; biologické markery; Extracellular Matrix Proteins; Heart Ventricles; lidé středního věku; srdeční selhání; Calcium-Binding Proteins; fibromodulin; Biomarkers; Female; Aged; transplantace srdce; Heart Failure; lidé; Male; Ventricular Function, Left